De novo assembly and comparative analysis of the Ceratodon purpureus transcriptome. (13th June 2014) - Szövényi, Péter; Perroud, Pierre‐François; Symeonidi, Aikaterini; Stevenson, Sean; Quatrano, Ralph S.; Rensing, Stefan A.; Cuming, Andrew C.; McDaniel, Stuart F.
Abstract The bryophytes are a morphologically and ecologically diverse group of plants that have recently emerged as major model systems for a variety of biological processes. In particular, the genome sequence of the moss, Physcomitrella patens, has significantly enhanced our understanding of the evolution of developmental processes in land plants. However, to fully explore the diversity within bryophytes, we need additional genomic resources. Here, we describe analyses of the transcriptomes of a male and a female isolate of the moss, Ceratodon purpureus, generated using the 454 FLX technology. Comparative analyses between C. purpureus and P. patens indicated that this strategy generated nearly complete coverage of the protonemal transcriptome. An analysis of the overlap in gene sets between C. purpureus and P. patens provides new insights into the evolution of gene family composition across the land plants. In spite of the overall transcriptomic similarity between the two species, Ka/Ks analysis of P. patens and C. purpureus suggests considerable physiological and developmental divergence. Additionally, while the codon usage was very similar between these two mosses, C. purpureus genes showed a slightly greater codon usage bias than P. patens genes potentially because of the contrasting mating system of the two species. Finally, we found evidence of a genome doubling 65–76 MYA that likely coincided with the contemporaneous polyploidy event inferred for P. patens but postdates the divergence of P. patens and C. purpureus. The powerful laboratory tools now available for C. purpureus will enable the research community to fully exploit these genomic resources.